#### Answer

(4,6)

#### Work Step by Step

You have two equations: 4x=3y-2 and 3x+y=18. Isolate y in the second equation in order to be able to substitute it into the first equation:
3x+y=18 -subtract 3x from both sides-
y=-3x+18
Substitute the equation into the first equation:
4x=3y-2 -substitute-
4x=3(-3x+18)-2 -distribute-
4x=-9x+54-2 -simplify like terms-
4x=-9x+52 -add 9x to both sides-
13x=52 -divide both sides by 13-
x=4
Plug in x=4 into one of the equations to solve for y:
3(4)+y=18
12+y=18
y=6
The solution is (4,6)